2023
DOI: 10.3390/molecules28041731
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds from New Natural Sources—Plant Genotype and Ontogenetic Variation

Abstract: Phenolic compounds (PCs) are widespread secondary metabolites with potent biological activity. Their sources are mainly plants from cultivated and natural states, providing valuable protective and health-promoting extracts. The wide biological activity of PCs (antioxidant, anti-inflammatory, antimicrobial, antiatherosclerotic, antidiabetic, antiallergic, prebiotic, antimutagenic) means that new sources of PCs are constantly being sought, as exemplified by extracting these compounds from tissue culture or agric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 102 publications
0
17
0
Order By: Relevance
“…A peak was detected at 2925 cm −1 before the reaction, which signified the aromatic C–H bending in phenolic compounds. HCR contains phenolic compounds, such as quinic acid, caffeic acid, chlorogenic acid, catechin and quercetin, which act as strong reducing agents (Nurzyńska‐Wierdak, 2023). Visible distinctions were also observed at 1645 and 1514 cm −1 , which were linked to N–H bending and C–C stretching, indicating the presence of primary amines and hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
“…A peak was detected at 2925 cm −1 before the reaction, which signified the aromatic C–H bending in phenolic compounds. HCR contains phenolic compounds, such as quinic acid, caffeic acid, chlorogenic acid, catechin and quercetin, which act as strong reducing agents (Nurzyńska‐Wierdak, 2023). Visible distinctions were also observed at 1645 and 1514 cm −1 , which were linked to N–H bending and C–C stretching, indicating the presence of primary amines and hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
“…Although at the qualitative level, all the phenolic compounds identified in the four ecotypes under study have been previously reported in the Lavandula genus, differences were observed in the concentration at which they were quantified. Variations in the qualitative and quantitative phenolic profile can be attributed to different factors, including genetic (inter and intraspecific variability) and physiological and development stages of the plants [ 32 ]. Thus, depending on the geographical origin of the plant material, differences in agronomic behavior and chemical composition are expected.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity potency of the plant extracts was assayed with referenced studies. Briefly, for DPPH radical scavenging activity, the reaction components created with varying volumes (10,20,40,80, and 120 μL) from stock extract solutions (mg mL À 1 ), 1 mL of DPPH solution (260 μM), and ethanol. The tubes were vigorously mixed, the reduction in color intensity caused by DPPH reacting with the tested antioxidant compound was read spectrophotometrically at 517 nm after 30 min in dark conditions.…”
Section: Antioxidant Capacity Of Endemic Plantsmentioning
confidence: 99%
“…[7] The bioactivity values of plants may be linked to their secondary ingredients, and they demonstrate various inhibitory effects such as antimicrobial, anticancer, antioxidant, and prevention of some diseases such as Alzheimer, diabetes, and cardiovascular associated with enzyme inhibition ability. [4,10] The curative properties of compounds such as captopril, tacrine, and acarbose are due to the inhibition of enzymes in the biochemical pathway. Therefore, inhibition of enzymes such as cholinesterase, glucosidase, and urease have pharmacological importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation